MANAGING ICT LITERACY PROGRAMS FOR TEACHERS: A STRATEGIC APPROACH TO ENHANCING LEARNING QUALITY IN THE MERDEKA CURRICULUM ERA - Raden Nurcahyo Yogayanto; Deny Hadi Siswanto; Kintoko Kintoko (CV. Denasya Smart Publisher, 2026)
This study aims to explore the management of the Information and Communication Technology (ICT) literacy program for teachers at SMA Muhammadiyah Mlati. Using a qualitative descriptive case study, data were gathered through in-depth interviews, classroom observations, and documentation analysis. Findings reveal that the program is managed through a managed through a systematic cycle: needs-based planning, collaborative implementation (including peer mentoring and hands-on practice), and reflective evaluation via academic supervision. The program is integrated into the school’s work plan (RKS) and aligns with the Merdeka Curriculum. Results indicate that the initiative significantly enhances teachers' pedagogical-digital competencies, fostering interactive and student-centered learning environments. However, challenges such as varying teacher proficiency levels, limited training time, and infrastructure constraints persist. The study concludes that consistent managerial support, tiered training, and strengthened teacher learning communities are essential for sustainability. This research affirms ICT literacy as a strategic educational management tool to improve learning quality in the digital era.